An overview of wire arc additive manufacturing (WAAM) in shipbuilding industry - Taşdemir, Ahmet; Nohut, Serkan (Ships and offshore structures, 2021)
Increasing competition in the international shipbuilding industry pushes the naval architect's pressure to reduce the costs of design and manufacturing of new buildings. Using newly developed Additive Manufacturing (AM) methods in the framework of industry 4.0 revolution can offer new opportunities in the manufacturing of labour-intensive and complex parts. Wire Arc Additive Manufacturing (WAAM) is a promising candidate for the manufacturing of large-scale metal parts, especially complicated double-curved parts (e.g. bulbous bow, propeller, rudder, etc.), in a more design flexible and cost-effective way in the shipbuilding industry. This article reviews the new developments of WAAM technology and discusses the feasibility of application of WAAM in the shipbuilding industry in the framework of material availability and properties, design complexity and cost by giving current and possible future applications.